Upaya Pemberdayaan Masyarakat Pesisir Untuk Mengurangi Sampah Melalui Gerakan Bersih Pantai - Silfia Septiani; Susilawati Susilawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Garbage is the biggest threat, especially in Indonesia, statistically the second largest country in the world after China. Most of Indonesia's population lives in coastal areas and that is where most of the trash is found. Garbage on the coast can come from human activities such as tourists, municipal waste disposal and part of the river. The purpose of this research is to increase awareness and participation to create a clean environment to protect clean coastal and estuarine environments. The research method is library research with a systematic review design based on descriptive analysis, namely journal articles searched in the Google Scholar database. The results of the study applying the clean movement can minimize waste, and appeal to the public to have a sense of concern for the environment so that the beach is not polluted, does not damage the environment and maintains public health.